Motor cortex outputs evoked by long-duration microstimulation encode synergistic muscle activation patterns not controlled movement trajectories - Capaday, Charles (Frontiers in Computational Neuroscience, 2022)
The effects of intracortical microstimulation (ICMS) parameters on the evoked electromyographic (EMG) responses and resulting limb movement was investigated. In Ketamine anesthetized cats, paw movement kinematics in 3D and EMG activity from 8-12 forelimb muscles evoked by ICMS applied to the forelimb area of the cat motor cortex (MCx) were recorded. The EMG responses evoked by ICMS were also compared to those evoked by focal ictal bursts induced by the iontophoretic ejection of the GABAA receptor antagonist Bicuculline methochloride (BIC) at the same cortical point. The effects of different initial limb starting locations on movement trajectories resulting from long-duration ICMS were also studied. ICMS duration did not affect the evoked muscle activation pattern (MAP). Short (50 ms) and long (500 ms) stimulus trains activated the same muscles in the same proportions. MAPs could, however, be modified by gradually increasing stimulus intensity. MAPs evoked by focal ictal bursts were also highly correlated with those obtained by ICMS at the same cortical point. Varying the initial position of the forelimb did not change the MAPs evoked from a cortical point. Consequently, the evoked movements reached nearly the same final end point and posture, with variability. However, the movement trajectories were quite different depending on the initial limb configuration and starting position of the paw. The evoked movement trajectory was most natural when the forelimb lay pendant ~ perpendicular to the ground (i.e. in equilibrium with the gravitational force). From other starting positions the movements did not appear natural. These observations demonstrate that whilst the output of cortical point evokes a seemingly coordinated limb movement from a rest position, it does not specify a particular movement direction, or a controlled trajectory from other initial positions.